
¬ G (p → ¬ q U p)

Equivalent:
¬ G (p → ¬ q U p) 
Complement: 
NBW 

G (p ∧ X ¬ p)

Equivalent:
G (p ∧ X ¬ p) 
Complement: 
NBW 

G (¬ p ∨ ¬ q) ∧ G (¬ p ∨ ¬ r) ∧ G (¬ q ∨ ¬ r)

Equivalent:
G (¬ p ∨ ¬ q) ∧ G (¬ p ∨ ¬ r) ∧ G (¬ q ∨ ¬ r) 
Complement:
¬ (G (¬ p ∨ ¬ q) ∧ G (¬ p ∨ ¬ r) ∧ G (¬ q ∨ ¬ r))

NBW 

p ∧ q ∧ Fr

Equivalent:
p ∧ q ∧ Fr 
Complement: 
NBW 

F (p → Fq)

Equivalent:
F (p → Fq) 
Complement: 
DBW 

¬ G (¬ p → q)

Equivalent:
¬ G (¬ p → q) 
Complement: 
DBW 

G p ∧ q

Equivalent:
G p ∧ q 
Complement: 
NBW 

G p ∧ ¬ q

Equivalent:
G p ∧ ¬ q 
Complement: 
NBW 

¬ p ∧ G q

Equivalent:
¬ p ∧ G q 
Complement: 
NBW 

F (¬ p ∨ q)

Equivalent:
F (¬ p ∨ q) 
Complement: 
DBW 

G ¬ p ∧ ¬ q

Equivalent:
G ¬ p ∧ ¬ q 
Complement: 
NBW 

(p ∨ q) U (¬ q ∧ ¬ p)

Equivalent:
(p ∨ q) U (¬ q ∧ ¬ p) 
Complement: 
DBW 

¬ p W (p ∧ ¬ q)

Equivalent:
¬ p W (p ∧ ¬ q) 
Complement: 
NBW 

(p ∧ q) U (p ∨ q)

Equivalent:
(p ∧ q) U (p ∨ q) 
Complement: 
NBW 

¬ l1 S l1

Equivalent:
¬ l1 S l1 
Complement: 
NBW 